S114 Hypoxia drives neutrophil-mediated endothelial damage in copd. (15th November 2017) - Lodge, KM; Hoenderdos, K; Robbins, AJ; Chilvers, ER; Li, W; Condliffe, AM
Abstract : Introduction: COPD is a progressive neutrophilic lung disease associated with increased risk of cardiovascular complications. Neutrophil elastase (NE) is implicated in COPD pathogenesis but the precise mechanisms of neutrophil-mediated tissue damage are unknown, particularly with respect to systemic manifestations. Inflamed COPD airways are profoundly hypoxic. We therefore hypothesised that hypoxia synergises with inflammatory cytokines to promote a destructive neutrophil phenotype with enhanced capacity for tissue damage, both locally and systemically. Methods: Neutrophils isolated from exacerbating COPD patients and age/sex-matched healthy volunteers were incubated under normoxia (21% O2 ) or hypoxia (0.8% O2 ) for 4 hours, before treatment with priming (PAF) and stimulating (fMLP) agents, with/without PI3Kinase inhibitors. NE activity was measured by Enzchek assay. Neutrophil supernatants were incubated with primary human pulmonary artery endothelial cells (HPAEC); cell damage was assessed by confocal microscopy. Normoxic/hypoxic neutrophil supernatants underwent tandem mass tag-labelled mass spectrometry (TMT-MS), and identified protein abundance was quantified. Neutrophil-derived microparticles (NDMPs) were isolated by ultra-centrifugation and quantified by NanoSight nanoparticle tracking technology. Results: Hypoxia increased NE release in a PI3K-dependent manner, with significantly more NE secreted by hypoxic neutrophils from exacerbating COPD patients versus healthy controls (p<0.0001). Supernatants generated from hypoxic, but not normoxic, stimulated neutrophils induced extensive HPAEC damage. Comparing the secretomes of supernatants derived from normoxic/hypoxic stimulated neutrophils, TMT-MS identified several additional proteins with potential to cause tissue damage as upregulated in hypoxia, including resistin and NGAL (neutrophil gelatinase-associated lipocalin). Notably, several of these proteins were not granule-associated, and some granule proteins were downregulated in hypoxia, indicating additional/alternative release mechanisms. Preliminary data show an increase in NDMP release under hypoxia, potentially contributing to the observed differential protein release. Conclusions: Hypoxia augments NE release in a PI3K-dependent manner, further increased during COPD exacerbations, and hypoxic neutrophil supernatants injure endothelial cells in vitro . Unbiased characterisation of hypoxic neutrophil secretomes identified several upregulated proteins which may contribute to cellular/tissue damage. In addition to degranulation, NDMP release may underpin differential protein secretion under hypoxia. Hypoxia engenders a neutrophil phenotype with potential to cause local and distant tissue damage in COPD; novel targets in the hypoxic neutrophil secretome may identify new therapeutic opportunities.